2000
DOI: 10.1002/1096-8644(200009)113:1<79::aid-ajpa7>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

On statistical methods for comparison of intrasample morphometric variability: Zalavár revisited

Abstract: In studies of morphology, methods for comparing amounts of variability are often important. Three different ways of utilizing determinants of covariance matrices for testing for surplus variability in a hypothesis sample compared to a reference sample are presented: an F-test based on standardized generalized variances, a parametric bootstrap based on draws on Wishart matrices, and a nonparametric bootstrap. The F-test based on standardized generalized variances and the Wishart-based bootstrap are applicable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
1
11
0
Order By: Relevance
“…The approach is useful because it allows the variables driving the increased variation to be identified and provides eigenvectors that allow subsidiary hypotheses about internal biological structure and relationships to be addressed using inferential statistics or graphical methods. That the method is comparative, i.e., requiring knowledge of ''baseline'' variability and a baseline covariance matrix, is problematic and the use of chi-square test statistics limits the application of this model to larger samples (Petersen, 2000). Raemsch (1995) used sample covariance matrix determinants, a scalar that reflects the overall level of variability represented within the matrix (Green, 1976b), which can be compared by bootstrapping the log of the ratio of two determinants (see Konigsberg, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach is useful because it allows the variables driving the increased variation to be identified and provides eigenvectors that allow subsidiary hypotheses about internal biological structure and relationships to be addressed using inferential statistics or graphical methods. That the method is comparative, i.e., requiring knowledge of ''baseline'' variability and a baseline covariance matrix, is problematic and the use of chi-square test statistics limits the application of this model to larger samples (Petersen, 2000). Raemsch (1995) used sample covariance matrix determinants, a scalar that reflects the overall level of variability represented within the matrix (Green, 1976b), which can be compared by bootstrapping the log of the ratio of two determinants (see Konigsberg, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Determinant ratio analysis was discussed above in the context of postmarital residence where it has been most heavily used. Petersen (2000) presented three variants of analysis of phenotypic variability. The first uses an F test statistic based on the ratio of standardized variances, assumes multivariate normality and is preferable only when sample sizes are large and aggregate summary statistics are available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive ln(|C♂|/|C ♀| ) reflects higher male mobility, a negative ln(|C♂|/|C ♀| ) reflects higher female mobility and a ln(|C♂|/|C ♀| ) equal to 0 reflects equal mobility between the sexes (Schillaci & Stojanowski, : 8, based on Konigsberg, ). Using the same R‐script, the original data matrix is then resampled through bootstrapping (for 999 iterations) to create a randomised distribution of determinant ratio values to assess statistical significance (Konigsberg, ; Petersen, ).…”
Section: Methodsmentioning
confidence: 97%
“…It also tests the cumulative contribution of each eigenvalue to the overall heterogeneity. However, Petersen (1998, 2000) recently criticized their methods and suggested that an F‐test would be more appropriate when dealing with small sample sizes. He also noted that Key and Jantz (1990a,b) utilized the wrong number of degrees of freedom (df) for the χ 2 test.…”
Section: Intragroup Variabilitymentioning
confidence: 99%